2005
DOI: 10.1002/cbf.1147
|View full text |Cite
|
Sign up to set email alerts
|

A review of HIV-1 Tat protein biological effects

Abstract: The authors have reviewed some biological properties of HIV-1 Tat protein, and have also reported some personal data. This viral regulatory protein is endowed with multifunctional activities, acting as an endogenous factor in the infected cells and exogenously, on those uninfected. In particular, Tat-induced proliferation and differentiation of HIV target cells which promotes viral infection, is discussed in this review. However, exogenous Tat protein can sometimes also produce, directly or indirectly, damagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 49 publications
3
50
0
Order By: Relevance
“…73,74 Although no studies have 73,75 Recently available transgenic mice expressing the HIV-1 Vpr protein in adipose tissues and in the liver show altered systemic lipid metabolism. 76 Vpr is also a known inducer of apoptosis through activation of the mitochondrial permeability transition pore (MPTP) 77 and therefore may contribute to adipocyte apoptosis in HALS, although this issue has not yet been addressed in adipose cells.…”
Section: Lipomatosis In Hals Reveals a Potential For Brown Adipocyte mentioning
confidence: 99%
“…73,74 Although no studies have 73,75 Recently available transgenic mice expressing the HIV-1 Vpr protein in adipose tissues and in the liver show altered systemic lipid metabolism. 76 Vpr is also a known inducer of apoptosis through activation of the mitochondrial permeability transition pore (MPTP) 77 and therefore may contribute to adipocyte apoptosis in HALS, although this issue has not yet been addressed in adipose cells.…”
Section: Lipomatosis In Hals Reveals a Potential For Brown Adipocyte mentioning
confidence: 99%
“…Once infected, these cells produce and secrete chemokines, cytokines, and other toxic factors, including the viral trans-activating protein (Tat) and HIV glycoprotein 120 (Gp120) that collectively play critical roles in the progression of HIV infection by directly altering immune homeostasis. HIV-1 Tat (trans-activating factor) is a regulatory protein that is indispensible for viral replication and gene expression (reviewed in Pugliese et al, 2005). This protein, once secreted, is highly immunogenic and induces the production of proinflammatory cytokines and chemokines in astrocytes (El-Hage et al, 2006), monocytes (Lafrenie et al, 1997), microglia (reviewed in Minghetti et al, 2004), and T lymphocytes (Kim et al, 2004).…”
mentioning
confidence: 99%
“…The role of Tat in apoptosis becomes more complicated in the CNS. Despite the adverse effects of Tat protein on the CNS, it has been shown that Tat binds to Bcl-X L , an antiapoptotic member of the Bcl-2 family, and forms a complex capable of inhibiting apoptosis in neuronal cells both in vitro and in vivo (Pugliese et al, 2005). Cantaluppi et al (2001) have shown that Tat, in a dosedependent manner, protects Kaposi's sarcoma (KS) cell lines and human umbilical vein endothelial cells from apoptosis induced by vincristine or serum starvation, respectively.…”
Section: Apoptosis Inhibition By Tatmentioning
confidence: 99%
“…1). The first exon encodes the first 72 aa (Pugliese et al, 2005;Schwarze et al, 1999). Due to the variable length of Tat, its weight varies from 14 to 16 kDa.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation